دور المؤسسات العمومية الصغيرة والمتوسطة الجزائرية في التنمية الاقتصادية: The role of Algerian small and medium public enterprises in economic development - بوهراوة زورة (Journal of North African Economies, 2025)
This research aims to reveal the contribution of small and medium-sized public enterprises to economic development in Algeria, by identifying the nature of their growth and their contribution to employment and value creation during the period 2012 - 2019. Among the findings: There is a continuous decrease in the number of public SME institutions during the study period. The category affected by this decrease is institutions which employ 50-250 workers. This continuous and significant decrease in the number of institutions leads to the referral of a large number of unemployed workers. It also reduced the realization of added value compared to SMEs of private enterprises, which negatively affected economic development.